Inovasi Model Bisnis Media Cetak Ambon Ekspres Di Era Digital - Husein, Muhammad Iqbal (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
This research aims to identify and analyze the innovative business models the Ambon Ekspres print media applied in the digital information era. This research mainly focuses on understanding how Ambon Ekpsres can integrate digital technology into its operations and develop effective marketing strategies to create added value for readers and advertisers. Data from interviews, observations, and documents will be analyzed using thematic analysis techniques. These analysis steps include Transcription and Coding, Theme Grouping, and Narrative Arrangement. The results of this research show that print media needs to diversify its business relevant to modern society's needs. One thing that can be seen is the business strategy carried out by Ambon Ekspres print media, which is to maximize its digital content. In terms of company revenue, the contribution of digital content is still smaller than that of printed newspapers. However, the revenue growth trend continues to occur in line with the introduction and promotions carried out by management. Keywords: Innovation, Business Media